Pentingnya Pendidikan Karakter di Sekolah: Membangun Generasi Yang Beretika dan Bertanggung Jawab - Rahmania; Parhiyangan, Aura Putri; Izzatunnajiah; Suptiani, Yulinda; Azmi, Nazrul (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This research emphasizes the importance of character education as the main foundation in facing moral and social challenges in the era of globalization.Through a holistic approach, character education aims to develop positive values such as honesty, discipline, and empathy in students.Various methods of implementing character education in schools are discussed, including their impact on students' behavior in daily life.Effective character education is expected to produce individuals who are integrity-driven, wise in making decisions, and capable of making positive contributions to society.In addition, character education also supports the creation of an inclusive learning environment, values diversity, and builds harmonious social relationships.The success of character education implementation requires collaboration between teachers, parents, and the surrounding environment, so that noble values can be applied consistently.Thus, character education not only shapes the personality of students but also contributes to building a civilized society ready to face future challenges